VINTE ANOS DE CRISE: VOLATILIDADE ELEITORAL E MIGRAÇÃO PARTIDÁRIA NO SISTEMA PARTIDÁRIO SUBNACIONAL DE RONDÔNIA (1982-2002) - Saraiva Leão Viana, João Paulo (Suffragium - Scientific Journal of the Regional Electoral Court of Ceará (TRE-CE), 2026)
This article addresses the issue of party migration in Rondônia's party subsystem in the period between the 1982 and 2002 elections, in a comparative perspective characterized in the period as one of the most expressive cases of institutional fragility in the national party system. The text is divided into five sections, including an introduction and conclusion. In the second section, the study discusses the issue of electoral volatility and the Brazilian sub-national level. Next, the text presents aggregate data on political competition in Rondônia between 1982 and 2002. Subsequently, the debate focuses on post-1985 electoral-party legislation and party migration in the Brazilian political system. In this same section, the case of Rondonia during the 1983-2007 legislatures will be analyzed. Finally, we present some considerations about the relationship between electoral volatility and party migration in Rondonian politics between 1982 and 2007. It is important to emphasize that the study deals specifically with electoral disputes for the Chamber of Deputies and Legislative Assemblies between 1982 and 2002.Translated with DeepL.com (free version)